2020
DOI: 10.1108/ajar-03-2019-0022
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the financial soundness of the Kazakh banks

Abstract: PurposeThe contribution of the banking industry to the financial crisis of 2007/8 has raised public concerns about the financial soundness of banks around the world with many countries still suffering the backlogs of this crisis. The continuous emergence of such crises at both national and international levels increases governments', bank regulators' and financial market participants' need for reliable tools to assess the financial soundness of banks. In this context, this study investigates the financial soun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 20 publications
2
24
1
Order By: Relevance
“…Moreover, the findings of this study were relatively consistent with the findings of Salina et al (2021), which aimed to assess the financial soundness of Kazakhstani banks for the period 2008-2014. The study identified several accounting indicators that influenced the financial soundness of banks using Principal Component Analysis (PCA).…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 82%
See 3 more Smart Citations
“…Moreover, the findings of this study were relatively consistent with the findings of Salina et al (2021), which aimed to assess the financial soundness of Kazakhstani banks for the period 2008-2014. The study identified several accounting indicators that influenced the financial soundness of banks using Principal Component Analysis (PCA).…”
Section: Literature Review and Hypothesis Developmentsupporting
confidence: 82%
“…This assessment encompasses four primary dimensions namely capital indicators, asset quality indicators, return and profitability indicators, and liquidity indicators, as outlined in their annual reports (Palestine Monetary Authority-Publications, 2019). (Youssef, 2019), (Bouherira, 2020), (Ibrahim et al, 2021), (Khemis, 2021), (Kullab & Yan, 2018), (Rahman, 2017), (Ouma & Kirori, 2019), (Abusharbeh, 2020), (Almahadin et al, 2020), (Salina et al, 2021) Palestinian Monetary Authority Indicator References Source Nonperforming Loans Net of Provisions to Capital (Bouherira, 2020), (Kullab & Yan, 2018).…”
Section: Fsis Adopted By the Palestine Monetary Authoritymentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, weaknesses in accounting and auditing standards or the misuse of these standards will lead to the dissemination of asymmetric information among the internal and external stakeholders of the firm and, accordingly, making wrong investment decisions. These systemic wrong decisions will feed finance and the emergence of economic crises (see, Salina et al, 2020).…”
Section: Literaturementioning
confidence: 99%